Evaluating the In Vitro Potential of Natural Extracts to Protect Lipids from Oxidative Damage - Rafael Félix; Patrícia Valentão; Paula B. Andrade; Carina Félix; Sara C. Novais; Marco F. L. Lemos (MDPI AG, 2020)
Lipid peroxidation is a chemical reaction known to have negative impacts on living organisms’ health and on consumer products’ quality and safety. Therefore, it has been the subject of extensive scientific research concerning the possibilities to reduce it, both in vivo and in nonliving organic matrices. It can be started by a variety of oxidants, by both ROS-dependent and -independent pathways, all of them reviewed in this document. Another feature of this reaction is the capacity of lipid peroxyl radicals to react with the non-oxidized lipids, propagating the reaction even in the absence of an external trigger. Due to these specificities of lipid peroxidation, regular antioxidant strategies—although being helpful in controlling oxidative triggers—are not tailored to tackle this challenge. Thus, more suited antioxidant compounds or technologies are required and sought after by researchers, either in the fields of medicine and physiology, or in product development and biotechnology. Despite the existence of several laboratory procedures associated with the study of lipid peroxidation, a methodology to perform bioprospecting of natural products to prevent lipid peroxidation (a Lipid Peroxidation Inhibitory Potential assay, LPIP) is not yet well established. In this review, a critical look into the possibility of testing the capacity of natural products to inhibit lipid peroxidation is presented. In vitro systems used to peroxidize a lipid sample are also reviewed on the basis of lipid substrate origin, and, for each of them, procedural insights, oxidation initiation strategies, and lipid peroxidation extent monitoring are discussed.